A Label Free Colorimetric Assay for the Detection of Active Botulinum Neurotoxin Type A by SNAP-25 Conjugated Colloidal Gold - Halliwell, Jennifer (MDPI, 2013)
Botulinum neurotoxins are one of the most potent toxins known to man. Current methods of detection involve the quantification of the toxin but do not take into account the percentage of the toxin that is active. At present the assay used for monitoring the activity of the toxin is the mouse bioassay, which is lengthy and has ethical issues due to the use of live animals. This report demonstrates a novel assay that utilises the endopeptidase activity of the toxin to detect Botulinum neurotoxin in a pharmaceutical sample. The cleaving of SNAP-25 is monitored via UV-Visible spectroscopy with a limit of detection of 373 fg/mL and has been further developed into a high throughput method using a microplate reader detecting down to 600 fg/mL of active toxin. The results show clear differences between the toxin product and the placebo, which contains the pharmaceutical excipients human serum albumin and lactose, showing that the assay detects the active form of the toxin.